Sexual history evidence in rape trials: is the jury out? - Herriott, Charlotte (Routledge frontiers of criminal justice, 2023)
Chapter One - Introduction: Situating the DebateChapter Two ⁰́₃ Mock Jury Simulations: Insights through the Looking GlassChapter Three - Sexual History Evidence: "The Canary in the Criminal Justice Mine?"Chapter Four - Taking Stock: S.41 in OperationChapter Five - ⁰́₈No doesn⁰́₉t always mean no⁰́₉: Socio-Sexual Stereotypes and HeteronormativityChapter Six - ⁰́₈Was she that type of girl?⁰́₉: Sexual History Evidence and Constructions of Complainant CredibilityChapter Seven - Sexual History Evidence: A Complicating Factor? Chapter Eight - Lessons to be Learnt from Other Jurisdictions?Chapter Nine - Back to the Drawing Board?